Post hoc depression analysis from a pharmacist-led diabetes trial - M. Thomas Bateman, PharmD, BCACP; Caitlin McCarthy, PharmD, BCPP; Katherine M. Prioli, MS; Mary L. Wagner, MS, PharmD (American Association of Psychiatric Pharmacists, 2023)
Introduction: Diabetes and depression may present concurrently, and clinical pharmacists are well equipped to manage these conditions. Clinical pharmacists were grant funded to implement a diabetes-focused randomized controlled trial in a Federally Qualified Health Center. The objective of this analysis is to evaluate if glycemic control and depressive symptoms improve for patients with diabetes and depression with additional management from clinical pharmacists compared with those receiving the standard of care. Methods: This is a post hoc subgroup analysis of a diabetes-focused randomized controlled trial. Pharmacists enrolled patients with type 2 diabetes mellitus (T2DM) and a glycated hemoglobin (A1C) greater than 8% and randomly assigned them to 1 of 2 cohorts, one managed by the primary care provider alone and one with additional care from the pharmacist. Pharmacists completed encounters with patients who have T2DM with or without depression to comprehensively optimize pharmacotherapy while tracking glycemic and depressive outcomes throughout the study. Results: A1C improved from baseline to 6 months in patients with depressive symptoms who received additional care from pharmacists by -2.4 percentage points (SD, 2.41) compared with a -0.1 percentage point (SD, 1.78) reduction in the control arm (P .0081), and there was no change in depressive symptoms. Discussion: Patients with T2DM and depressive symptoms experienced better diabetes outcomes with additional pharmacist management compared with a similar cohort of patients with depressive symptoms, managed independently by primary care providers. These patients with diabetes and comorbid depression received a higher level of engagement and care from the pharmacists, which led to more therapeutic interventions.